2021
DOI: 10.1002/ejp.1731
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with seeking medical care for low back pain in a twin adult sample

Abstract: Background: Previous studies have only investigated how symptom presentation and socio-demographic factors influence care-seeking for low back pain (LBP).However, the influence of health and lifestyle factors remains unclear, and the potential confounding effects of aggregated familial factors (including genetics and the early shared environment) has not been considered extensively. Methods: A cross-sectional analysis was performed on 1605 twins enrolled in the Murcia Twin Registry (Spain). The outcome was see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 94 publications
(137 reference statements)
0
4
0
Order By: Relevance
“…to 1605 twins in the same country, found that a history of diabetes was negatively associated with the odds of seeking medical care for low back pain. 21 Theoretically, diabetes could lead to an increase in the risk of CLBP due to lower muscle mass 22 23 and poor mental health (eg, depression 13 24 ), while diabetes and CLBP share common risk factors such as obesity 25 26 and low-grade systemic inflammation. 27 28 Although previous studies have advanced the field, the majority of these studies were surveys, and the use of self-reported measures may have impacted the validity of their findings.…”
Section: Significance Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…to 1605 twins in the same country, found that a history of diabetes was negatively associated with the odds of seeking medical care for low back pain. 21 Theoretically, diabetes could lead to an increase in the risk of CLBP due to lower muscle mass 22 23 and poor mental health (eg, depression 13 24 ), while diabetes and CLBP share common risk factors such as obesity 25 26 and low-grade systemic inflammation. 27 28 Although previous studies have advanced the field, the majority of these studies were surveys, and the use of self-reported measures may have impacted the validity of their findings.…”
Section: Significance Of This Studymentioning
confidence: 99%
“…In recent years, a significant body of literature has focused on the relationship between diabetes and CLBP, and these studies have reported conflicting results. [14][15][16][17][18][19][20][21] For example, a Spanish study including 2096 twins revealed that type 2 diabetes was cross-sectionally associated with a wide range of back conditions such as severe CLBP and severe chronic spinal pain. 14 A systematic review and metaanalysis of eight studies also showed a positive association between diabetes and both low back and neck pain.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Covariates were chosen based on the potential association between physical activity and analgesic use and activity limitation for LBP. Previous research has shown that activity limitation and analgesic use for LBP can be associated with factors such as pain intensity (Monticone et al, 2021; Oliveira et al, 2019; Patterson et al, 2021; Severeijns et al, 2001; Sturgeon, 2014) and duration (Hayden et al, 2010; Sribastav et al, 2018), depression (Grabovac & Dorner, 2019; Monticone et al, 2021; Oliveira et al, 2019; Pinheiro et al, 2015; Severeijns et al, 2001; Sturgeon, 2014), anxiety (Grabovac & Dorner, 2019; Monticone et al, 2021; Oliveira et al, 2019; Severeijns et al, 2001; Sturgeon, 2014), stress (Grabovac & Dorner, 2019; Severeijns et al, 2001; Sturgeon, 2014), sleep quality (Ho et al, 2021; Kovacs et al, 2018; Patterson et al, 2021), level of disability (Ferreira et al, 2010; Monticone et al, 2021; Oliveira et al, 2019; Severeijns et al, 2001; Sturgeon, 2014), age (Mannion et al, 2013), gender (Ferreira et al, 2010; Ho et al, 2021; Mannion et al, 2013) and body mass index (BMI) (Hashimoto et al, 2018; Miura et al, 2019; Sribastav et al, 2018; Stevans et al, 2021). Therefore, the confounding effects of these aforementioned factors on analgesic use and activity limitation were accounted for in the study analysis.…”
Section: Methodsmentioning
confidence: 99%